2011
DOI: 10.1590/s0103-50532011000500017
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Lupane isolated from Combretum leprosum against Leishmania amazonensis promastigotes

Abstract: O presente trabalho descreve a atividade do extrato etanólico (EE) dos frutos de Combretum leprosum, do triterpeno 3b, 6b, 16b-triidroxilup-20(29)-eno (1) e seus derivados sintéticos (1a-1d), sobre promastigotas de Leishmania amazonensis. O EE apresentou atividade leishmanicida e o valor de IC 50 foi de 24,8 mg mL -1 . Já o triterpeno 3b, 6b, 16b-trihidroxilup-20(29)-eno (1), na concentração de 5,0 mg mL -1 , apresentou uma potente ação inibitória sobre a proliferação das promastigotas (IC 50 = 3,3 mg mL -1 ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
2
19
0
5
Order By: Relevance
“…The ethanolic extract was tested on a 25 μg/mL concentration and the lupane was tested on a 5 μg/ mL for citotoxicity. On these concentrations, neither the extract nor the lupane were toxic (TELES et al, 2011). The citotoxicity result of the ethanolic extract for Leishmania is also in agreement with our work.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The ethanolic extract was tested on a 25 μg/mL concentration and the lupane was tested on a 5 μg/ mL for citotoxicity. On these concentrations, neither the extract nor the lupane were toxic (TELES et al, 2011). The citotoxicity result of the ethanolic extract for Leishmania is also in agreement with our work.…”
Section: Resultssupporting
confidence: 92%
“…Triterpenes that were isolated from the genus Combretum also showed activities against another microorganisms, like fungi (BISOLI et al, 2008), bacteria (ANGEH et al, 2007a;ANGEH et al, 2007b;SONGCA, RAMURAFHI;OLUWAFEMI, 2013), viruses (ASRES;BUCAR, 2005) and other species of parasites (TELES et al, 2011;HAAVIKO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibiting activity of triterpenoids isolated is described for promastigotes [28,29] and intracellular amastigotes of Leishmania amazonensis [28]. amazonensis was inhibited (IC 50 = 67 µM) [31]. The anti-leishmanial activity of hexane fractions from M. linifera may be related to sequiterpenes and other terpenes ( Table 2 and Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…Torres-Santos et al (26) and Teles et al (29) investigated the effects of isolated triterpenes on promastigotes of L. amazonensis and found that the presence of the carboxylic acid grouping was associated with antiprotozoal activity. Pentacyclic triterpenes, with more hydroxyl groups, had greater effects on these promastigotes and this chemical characteristic is also present in tingenone B, which is a pentacyclic triterpene with a quinonamethide skeleton.…”
Section: Discussionmentioning
confidence: 99%